ERA-40 Monthly Means of 2.5 Degree Surface and Flux Analysis Data - European Centre For Medium-Range Weather Forecasts (UCAR/NCAR - Research Data Archive, 2004)
This dataset includes monthly means of 2.5 degree surface and flux analysis data from ECMWF ERA-40 reanalysis project.